Perancangan Sistem Informasi Akuntansi Penjualan Handphone pada Toko Java Phone - Fanny Fatma Wati; Andrian Eko Widodo; Nadiyah Hidayati; Mawadatul Maulidah; Recha Abriana Anggraini (LPPM UBSI Kampus Kota Tegal, 2026)
The rapid development of information technology encourages business actors to improve the quality of data management, including in the field of mobile phone sales. Java Phone Store still uses a manual system for recording sales transactions, which has the potential to cause recording errors, delays in report preparation, and less accurate financial information. Therefore, it is necessary to design an Accounting Information System for Sales that can overcome these problems and improve operational efficiency.This study aims to design a computerized sales accounting information system for Java Phone Store. The research methods used include observation, interviews, and literature study to collect relevant data. The system development method uses the waterfall model, which consists of requirement analysis, system design, implementation, and system testing stages.The results show that the designed system is able to manage product data, sales transactions, and generate sales reports automatically, quickly, and accurately. With this system, data processing becomes more efficient and minimizes errors that occur in the manual system. In conclusion, the implementation of this sales accounting information system is important to improve operational performance and the quality of financial information at Java Phone Store.